Investigation of combustion flame spray as in-situ repair technology for thermal barrier coatings - Fanicchia, Francesco (2018)
The continuous increase of Turbine Entry Temperature (TET) in aerospace gas-turbines is the main driver for the research effort in the development of coatings for thermal and oxidation protection: i.e. Thermal Barrier Coatings (TBC). The need for TBC is particularly relevant within the combustor assembly (or simply combustion chamber) where the highest temperatures within a gas turbine, in excess of 1700 C, are registered. Due to the harsh thermal and oxidative conditions experienced within the combustion chamber, TBC are subjected to several degradation mechanisms which generally result in spallation (or delamination) of the coating. Spallation is more likely to be observed at specific locations within a combustion chamber, and acceptance limits for this quantity are specified by the Original Equipment Manufacturer (OEM). To reduce the risk that coating spallation will lead to an unplanned engine removal, in-situ coating re-deposition may be possible. However, the development of such a technology poses significant challenges. The selected deposition process must, in fact, be able to operate in a confined environment (i.e. the combustion chamber) and produce TBC of microstructure providing adequate thermal and oxidation protection properties. Moreover, a deep understanding between the process parameters and both microstructure and shape of produced coating is necessary to achieve an optimum control over the whole deposition process. Therefore, after an initial selection of Combustion Flame Spray (CFS) as TBC deposition technology, the present thesis has the following objectives: (i) analysing in-depth the physics/chemistry of coating build-up at a microscopic level (i.e. single-splat) in order to relate this to fundamental properties (e.g. adhesion and residual stress) measured at macroscopic coating level, (ii) investigating the relationship between process parameters and their effect on the material properties of the deposit, in order to determine an optimum process parameters "window" and (iii) to develop a mathematical framework that accounts for the stochastic nature of the deposition process, and has the capability to predict the deposit growth geometry with high spatial accuracy for different process parameters. For coating build-up analysis purposes, a novel set of experimental tools is developed, allowing to model fundamental flattening and solidification mechanisms with a sub-micrometre spatial resolution. For deposition parameters optimisation purposes, an extensive experimental analysis of the effect of deposition parameters including: powder morphology (size and shape), equivalence ratio, powder feed rate, carrier gas flow and torch-to-substrate standoff distance has been performed for the CFS-produced TBC to complete the lack of knowledge in literature data. Finally, the deposit growth model allows to predict, in the time domain, the three-dimensional footprint (i.e. deposit shape) and temperature of CFS and generally thermal spray deposits. For this purpose, a three-dimensional implicit finite-difference algorithm, based on two interplaying geometrical and thermal-analysis sections, has been developed. The work of this thesis thus provides a step forward in the understanding of the thermal spray deposit formation process. In fact, the determined correlation between properties at both single splat and coating level represents a powerful tool making the optimisation of process parameters-coating properties relationship more efficient as opposed to traditional trial-and-error approaches. Moreover, the developed calibration-based deposit growth model results of simple application, opening the way for spray automation in difficult-to-spray geometries and/or repair applications for several thermal spray processes.